2011
DOI: 10.1021/ma200131e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Functional Polyethylenes by Catalytic Copolymerization

Abstract: b S Supporting Information T he physical properties of polyethylene (PE) can be drastically altered by careful manipulation of its microstructure and particularly by controlling the length and distribution of alkyl branches along the chain. Instead of alkyl chains, it would be desirable to introduce low amounts of polar groups because they are expected to greatly impact the toughness, flexibility, crack resistance, gas permeability, miscibility, adhesion, and paintability of PE. 1 These copolymers are also of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…The polymer is prepared by the terpolymerization of ethylene, NBE, and 5‐ exo norbornene methyl alcohol ( exo ‐NBE‐CH 2 OH), using a phosphine sulfonate catalyst (Scheme ). The choice of this catalyst is motivated by the observation that phosphine sulfonate catalysts offer unprecedented functional group tolerance for the copolymerization of a wide range of polar olefins with ethylene and most notably for the copolymerization of ethylene with NBE …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymer is prepared by the terpolymerization of ethylene, NBE, and 5‐ exo norbornene methyl alcohol ( exo ‐NBE‐CH 2 OH), using a phosphine sulfonate catalyst (Scheme ). The choice of this catalyst is motivated by the observation that phosphine sulfonate catalysts offer unprecedented functional group tolerance for the copolymerization of a wide range of polar olefins with ethylene and most notably for the copolymerization of ethylene with NBE …”
Section: Resultsmentioning
confidence: 99%
“…The choice of this catalyst is motivated by the observation that phosphine sulfonate catalysts offer unprecedented functional group tolerance for the copolymerization of a wide range of polar olefins with ethylene 29,30,[32][33][34][35][36][37][38][39][40][41][42][43][44] and most notably for the copolymerization of ethylene with NBE. 42,[45][46][47] Initial experiments aimed at preparing a NBE monomer containing a SO 3 H group. Since it has recently been demonstrated by the group of Tritto that the reactivity of exo monomers is greater than endo monomers, 47 our monomer synthetic scheme was devised so as to obtain NBEs bearing a substituent exclusively in the 5-exo position.…”
Section: Copolymerization Of Ethylene With Nbementioning
confidence: 99%
“…Additionally, low polymerization activities are often observed due to reversible intra-and intermolecular deactivation by coordination of the functional groups present to the palladium center. Intriguingly, norbornene [13,14] and some of its functional derivatives, [15] such as norbornene anhydride, [16] are exceptions to these trends observed for other polar monomers such as acrylic acid, [17] maleic anhydride, [16] or acrylates. [6,18,19] Chain transfer is even less pronounced after the incorporation of a norbornene anhydride unit into the growing chain than for ethylene leading to an increase of molecular weight with increasing norbornene anhydride content in the copolymer.…”
Section: Introductionmentioning
confidence: 89%
“…Under pressure-reactor conditions,e xposure of L1Pd to 5bar of Eand 0.075 m of VF at 95 8 8Cresulted in the formation of ac opolymer with al ow VF incorporation of 0.4 mol %( Table 1, entry 1). Preliminary 1 Ha nd 13 CNMR spectra of this E-VF copolymer indicated that incorporated VF is overwhelmingly (95 %) located in both saturated (S) chain ends and unsaturated (US) chain ends,inaratio of ca. 1:1( S VF :US VF = 44 %:51 %).…”
mentioning
confidence: 92%